Digital Web sebagai Strategi Meningkatkan Jual Beli UMKM Yal Collection di Bukittinggi - Reni Puji Rahayu; Nicho Syaputra; Nailul Mardiah; Sularno; Rafidola Mareta Riesa (CV. ITTC INDONESIA, 2024)
Yal Collection, an MSME located in Pasar Aur Kuning, Bukittinggi, West Sumatra, only produces batik trousers with the aim of preserving local culture and improving the economy of the local community. Even though batik pants products have broad market potential, the Yal Collection faces challenges in terms of marketing, especially in utilizing digital platforms. Lack of skills in digital marketing and social media management hinders these MSMEs from reaching a wider market and increasing product competitiveness. This community service program aims to help Yal Collection strengthen its marketing strategy through digital marketing training which includes social media management, content optimization and online promotion strategies. The method used is a participatory approach, namely direct training and assistance in creating visual content and implementing digital marketing strategies. Results showed increased brand visibility, number of social media followers, and online product sales. In conclusion, proper strengthening of digital marketing can increase Yal Collection's competitiveness and expand the market for their products significantly .